(untitled) (MAUSAM, 1993)
The tracking of meteorological balloons using dipole matrix array antenna by sequential lobe switching with the help of a motor driven mechanical UHF phasing switch had been in operational use in our national upper air network from last 25 years. A solid state four-way electronic switch at 400 MHz using high conductance-high speed switching diodes has been designed to replace the aged motor driven mechanical phasing switch. Microstripline technique has been used in designing UHF switch to achieve proper impedance, matching, routing and addition of UHF signals received from the four antenna bays. For sequential switching of antenna array and synchronisation of data reception and display system the intelligence is generated by a compact logic in-built in the phasing switch. Unlike, mechanical switch, the present system has no switching noise and has low insertion loss (2 dB), thus improving the data acquisition capability of ground reception system. The design of switch is modular, light weight and highly rugged to suit all types of environmental conditions.